2004
DOI: 10.1051/forest:2004062
|View full text |Cite
|
Sign up to set email alerts
|

Fine root distribution, seasonal pattern and production in four plantations compared with a natural forest in Subtropical China

Abstract: -Fine root (< 2 mm in diameter) distribution, seasonal pattern and net production were studied during 1999-2001 in 33 year-old plantations of two coniferous trees, Chinese fir (Cunninghamia lanceolata, CF) and Fokienia hodginsii (FH) and two broadleaved trees, Ormosia xylocarpa (OX) and Castanopsis kawakamii (CK), and compared with that of an adjacent natural forest of Castanopsis kawakamii (NF, ~150 year old) in Sanming, Fujian, China. Fine root biomass and necromass were determined by soil coring at a bimont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 34 publications
8
47
2
1
Order By: Relevance
“…It is surprising that our results showed different patterns, that fine root biomass was highest in January and lowest in July in all the Chinese fir plantations. Although similar results also had been reported that the minimum value of fine root biomass generally appeared from May to July [40,43]. The fine root biomass dynamics were not only related to the fine root growth, but also the longevity and turnover rate, which merits further investigation.…”
Section: Fine Root Biomass and Necromasssupporting
confidence: 61%
See 1 more Smart Citation
“…It is surprising that our results showed different patterns, that fine root biomass was highest in January and lowest in July in all the Chinese fir plantations. Although similar results also had been reported that the minimum value of fine root biomass generally appeared from May to July [40,43]. The fine root biomass dynamics were not only related to the fine root growth, but also the longevity and turnover rate, which merits further investigation.…”
Section: Fine Root Biomass and Necromasssupporting
confidence: 61%
“…The studies on seasonal variations in root biomass had reported that stand ages were consistent with the seasonal variation pattern [40]. Fu et al [34] believed that low temperature is the influencing factor of fine root dynamics.…”
Section: Fine Root Biomass and Necromassmentioning
confidence: 91%
“…Yang et al (2004c) noted that the leaf-litter of Chinese fir possesses higher lignin concentration and lignin/N ratio than that of broad leaf tree. In addition, broadleaved trees may allocate more biomass to their roots, especially the fine roots at the shallow soil horizons, which can fix a greater amount of carbon and transfer more root detritus to the top soil (Yang et al, 2004a(Yang et al, , 2004b.…”
Section: Discussionmentioning
confidence: 99%
“…Fine root (< 2 mm) biomass was measured by the sequential core method [49]. On each sampling date, 30 soil cores (1 m in depth) were randomly collected from each forest bimonthly during January 1999-January 2002 using a steel corer (6.8 cm diameter, 1.2 m length).…”
Section: Belowground Litterfallmentioning
confidence: 99%
“…We had reported litterfall and fine-root dynamics and soil biological changes on these forests [8,49,51]. The primary objective of this study was to determine if plantations consisting of broadleaved and coniferous species altered the ecosystem C stocks.…”
Section: Introductionmentioning
confidence: 99%